Burkholderia pseudomallei in cystic fibrosis and treatment complications. Issue 1 (30th November 2014) - Radhakrishna, Naghmeh; Morton, Judith
Abstract A healthy 29‐year‐old Australian man with cystic fibrosis (CF) grew Burkholderia pseudomallei on a routine sputum culture 1 month after returning from holiday in Thailand. He underwent a 12‐month treatment regime with multiple antibiotics resulting in a number of adverse events. Sputum cultures were cleared of the pathogen and remain negative 8 years post‐treatment. There were no clinical sequelae and no deterioration in lung function. Few reports have been published to date on melioidosis in CF patients. The proposed management for this infection includes multiple antibiotics regimens for prolonged periods of time, which may result in adverse events. Optimal treatment and length of treatment are currently determined on an individual basis.